IMPLEMENTASI MODEL MISSOURI MATHEMATICS PROJECT DENGAN METODE INQUIRY PADA KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Nur Fitriyan, Reska Umi Satania, Sukasno, (Epsilon: Jurnal Pendidikan Matematika, 2019)
Abstract: This research is motivated by the low ability to solve mathematical problems. The formulation of the problem in this study is Is the ability to solve math problems of VIII grade students of SMP Negeri 2 Lubuklinggau after applying the Missouri Mathematics Project model with the Inquiry method in the good category ?. This type of research is in the form of quasi-experimental conducted without the comparison group. The population is all eighth grade students of SMP Negeri 2 Lubuklinggau in the academic year 2019/2020 with a total of 375 students. As a sample is class VIII 1 with 36 students taken at random. Data collection is carried out by using a descriptive test technique. The collected data were analyzed using t-test at the level of confidence Î± = 0.05. From the results of data analysis, it can be concluded that the mathematics problem solving ability of VIII grade students of SMP Negeri 2 Lubuklinggau after following the Missouri Mathematics Project model with Inquiry method is in good category. The average value of the ability to solve problems after being given a treatment of 75.39, the percentage of the number of students with good and very good categories amounted to 77.78%.